Systemic interventions addressing market access challenges of smallholder vegetable farmers in Northern Vietnam. (2015) - Ha, Tuan M.; Bosch, Ockie J.H.; Nguyen, Nam C.
This study was conducted in Thai Nguyen (Vietnam) to determine appropriate interventions for promoting effective clean vegetable production and sales. A systems tool, stakeholder analysis and engagement were employed. Relevant stakeholders were involved to analyse the challenges of market access for safe vegetables. As a result, the problem was multifaceted and related to different stakeholders. The main leverage points for systemic interventions defined include awareness raising for all parties concerned, organised production for reduced input costs, addressing consumer demands, market actor linkages and quality control in accordance with policy recommendations. This research served as a case study for policy recommendations and institutional arrangements of local governments and stakeholders to better support smallholder farmers. The participatory approach created a co-learning environment where participating members can share their views, concerns and learn from other throughout the discussion and decision making processes. Contributions to organisational learning theory and knowledge creation are also discussed.